Substantial increase in wildfire danger conditions under anthropogenic climate change in Southwest France - Marine Lanet; Laurent Li; Hervé Le Treut (npj Natural Hazards)
Abstract Wildfires are an increasing concern under climate change, which may raise the frequency and intensity of fire-prone conditions. Here we assess summer wildfire danger evolution in Southwestern France under three climate scenarios (Representative Concentration Pathways RCP2.6, RCP4.5 and RCP8.5), using six climate models. Alongside the Fire Weather Index (FWI), widely used by operational services to assess daily fire danger, a complementary index, SM6-T3-VPD3 (soil moisture integrated backward to 6 months, surface air temperature and vapour pressure deficit backward to 3 months), is also used to assess prolonged hot and dry conditions. Results indicate that under the highest emission scenario, the probability of extreme compound hot and dry events increases from 0.04 to 0.49 in August during the twenty-first century. Even under the lowest emission scenario, their likelihood increases from 0.03 to 0.15. Therefore, this study underscores the importance and complementarity of mitigation and adaptation strategies in addressing wildfire danger.